Uczestniczki i uczestnicy procesu kształcenia wobec wyzwań kształcenia zdalnego - Porzucek-Miśkiewicz, Maria (Kultura-Społeczeństwo-Edukacja, 2021)
The article presents the results of study on the challenges faced by distance learning. It was carried out by means of a proprietary online questionnaire among students of pedagogy of the Faculty of Educational Studies at the University of Adam Mickiewicz in Poznań. Conclusions drawn on the basic research results may be helpful in understanding the well-being of students during distance learning.